Evidences of accumulation points in cascade regenerative phenomena observed in high voltage dc devices insulated by long vacuum gaps. (5th November 2018) - Pilan, N; De Ambrosis, S; De Lorenzi, A; Cavenago, M; Fincato, M; Fontana, C; Lotto, L; Martines, E; Pasqualotto, R; Pino, F; Rossetto, F; Spada, E; et al.
Abstract: Localized heating has been observed in unexpected positions on anodic surfaces in a multi-electrode device insulated by vacuum gaps. In double polarity experiments, a counter-intuitive behavior of current-voltage characteristic has also been observed. The phenomena could depend on a cascade effect of charged particles exchanged between electrodes and on a mutual correlation of particle trajectories between electrode surfaces occurring during the high voltage conditioning phase. Attractors regions ascribed to regenerative processes of charged particles between cathode and anode have been identified thanks to numerical simulations The position of the attractors depends only on electrode shape and the ratios of applied voltages. This finding suggests new perspectives in neutrons sources applications, where recurrent impacts of focused high energy hydrogen isotopes take place on solid hydride targets supported by metallic electrodes insulated by vacuum gaps.